(untitled) (Research, Society and Development, 2021)
The objective of this study is to promote both life and health quality to hemodialysis patients, thus offering them a safe sharing space and a social safe environment, due to their Chronic Kidney Failure condition. To achieve this paper’a objective, the researches promoted psychological interventions and sessions of art therapy. Both tools worked as ways to ponder about mental health. The study was carried from March to June of 2019, and tried to unveil the meaningful links between the patients’ interviews and their composition of autobiographical books. The methodological approach of this study may be described as qualitative, its development was based in a field research. The reassert was approved by the Brazilian Ethics and Research Committee (Comitê de Ética e Pesquisa - CEP) under the following number CAEE 12389219.5.0000.5495. A number of 90 patients in Chronic Kidney Failure, of a Brazilian clinic, were invited to take part on the research. The psychological intervention produced a project called “biografia” in which the participants composed an autobiographical book of their life stories. The project was used to promote ways for the participants to think about the concepts of health and disease in their lives and to signify those concepts through Life Skills and Health Psychology. The materials and techniques of this study may be described as psychological interventions (active listening, welcoming and reflections) semi-structured interviews opened in depth, semi-structured script, observation, transcriptions, field diaries, and the use of graphic materials for art therapy handled by the participants to make the covers of the participants books. The results show the efficiency of psychological interventions based on arts and how such interventions may promote health and life quality to the participants when it comes to redeem their identity.